2021
DOI: 10.7150/ijbs.64077
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in colorectal cancer: current achievements and future perspective

Abstract: Following dramatic success in many types of advanced solid tumors, interest in immunotherapy for the treatment of colorectal cancer (CRC) is increasingly growing. Given the compelling long-term durable remission, two programmed cell death 1 (PD-1)-blocking antibodies, pembrolizumab and nivolumab (with or without Ipilimumab), have been approved for the treatment of patients with metastatic colorectal cancer (mCRC) that is mismatch-repair-deficient and microsatellite instability-high (dMMR-MSI-H). Practice-chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(126 citation statements)
references
References 100 publications
2
124
0
Order By: Relevance
“…It was similar to the results reported by Wang et al. ( 35 )and further confirmed that ICIs in combination with other therapeutic modalities were the most popular direction of research in this field. Keyword burst and clustering showed that “immune checkpoint inhibitors”, “combination therapy”, and “drug therapy” were hot topics in this field and promised to be studied more deeply in the future.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was similar to the results reported by Wang et al. ( 35 )and further confirmed that ICIs in combination with other therapeutic modalities were the most popular direction of research in this field. Keyword burst and clustering showed that “immune checkpoint inhibitors”, “combination therapy”, and “drug therapy” were hot topics in this field and promised to be studied more deeply in the future.…”
Section: Introductionsupporting
confidence: 91%
“…A review of CRC immunotherapy by Ahui Fan et al. ( 35 ) also focused on the treatment of microsatellite unstable and microsatellite stable CRC, mainly surrounding various therapeutic approaches with ICIs. In addition, most CRC immunotherapies were associated with keywords such as PD-1blockade, MSI, and T cell ( 2 ), indicating that these aspects were the hot topics in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on these observations, it was suggested that MSI-H/dMMR CRCs might have a good response to ICIs. Following the results of several stage II trials, ICIs are considered a breakthrough strategy in the treatment of MSI-H/dMMR mCRC [45,46]. However, not all MSI-H/dMMR mCRC patients respond to ICIs, suggesting that a deeper knowledge of immune-related mechanisms is needed [47].…”
Section: Predictive/prognostic Biomarkers For Selecting Crc For Immun...mentioning
confidence: 99%
“…Even if the administration of ICIs in MSI-H/dMMR CRC patients is relatively recent, resistance to treatment was already reported. The clinical studies investigating ipilimumabnivolumab and pembrolizumab showed objective responses of 54.6% [45] and 40% [27], respectively. The results suggest that a group of MSI-H/dMMR CRC patients harbor mechanisms of resistance that impair immune antitumor activity [139].…”
Section: Resistance To Immunotherapymentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) block the checkpoint receptors that tumours use to evade the immune system, dampening T cell activation. However, despite rapid advancements in immunotherapy, durable response rates to ICIs remain low, especially in colorectal cancers which are typically microsatellite stable [2]. In order to address this, combination clinical trials are ongoing to assess which adjuvants can enhance responsiveness by increasing tumour immunogenicity.…”
Section: Introductionmentioning
confidence: 99%